EFFECT OF ANATOMO-TOPOGRAPHIC AND SONOGRAPHIC POLARITY OF THE THYROID NODULES ON THE THYROID MALIGNANCY BY EVALUATING ITS IMPRESSION ON THE RELATIONSHIP BETWEEN THE BETHESDA SYSTEM, TBSRTC, STRAIN ELASTOGRAPHY SCORE AND THE THYROID HISTOPATHOLOGY - Sengul Demet; Sengul Ilker (Sanamed, 2019)
Background:The goal is to evaluate the association between the topo-sonographic polarity of the thyroid nodules and the thyroid malignancy by analyzing its effect on The Bethesda System for Reporting Thyroid Cytopathology (TBSRTC), score of Strain Elastography (SE) for thyroid as Tsukuba Elasticity Score (TES), and histopathologic assessment.